Chinese Martial Art Training Failed to Improve Balance or Inhibit Falls in Older Adults. Issue 3 (June 2019) - Ma, Ada W. W.; Wang, Hsing-Kuo; Chen, Duan-Rung; Chen, Ya-Mei; Chak, Yvonne T. C.; Chan, Joan W. Y.; Yam, Timothy T. T.; Cheng, Yoyo T. Y.; Ganesan, Balasankar; Fong, Shirley S. M.
This randomized controlled trial explored the effects of a Ving Tsun (VT) Chinese martial art training program on reactive standing balance performance, postural muscle reflex contraction latency, leg muscle performance, balance confidence and falls in community-dwelling older adults. We randomly assigned 33 healthy older adults to either a VT group (mean age = 67.5 years) or a control group (mean age = 72.1 years). The VT group received two 1-hour VT training sessions per week for three months (24 sessions). Primary outcome measures collected before and after the intervention period were electromyographic muscle activation onset latencies of the hamstring and gastrocnemius and the center of pressure path, length and movement velocity in standing (reactive balance performance). Secondary outcome measures included isometric peak force and time to isometric peak force of the knee extensors and flexors, the Activities-Specific Balance Confidence Scale score, and fall history. Results revealed that the mean gastrocnemius muscle activation onset latency was significantly longer (22.53 ms) in the VT group after the intervention. The peak force of the knee flexors significantly increased (by 1.58 kg) in the control group over time but not in the VT group. The time to reach peak force in the knee flexors was significantly longer (by 0.51 s) in the control group (but not the VT group) at posttest compared with the pretest value. No other significant group, time, or group-by-time interaction effects were noted. We discussed possible reasons for the failure of three months of martial art training to benefit fall risks among these older adults.